Absence of EpCAM in cervical cancer cells is involved in slug induced epithelial-mesenchymal transition - Xian Liu; Qian Feng; Yanru Zhang; PengSheng Zheng; Nan Cui (Cancer Cell International)
Abstract Background Slug (Snai2) is a pivotal player in initiating epithelial-mesenchymal transition (EMT) through its trans-suppression effect on E-cadherin in various normal and malignant cells. In this study, the positive effect of Slug on promoting cell motility and metastasis in cervical cancer was further confirmed in this study. Methods RNA-Seq was performed to explore the potential molecules that participate in Slug-mediated EMT in cervical cancer cells. The negative correlation between Slug and EpCAM expression in cervical cancer cells was detected in this study, and linked them with in vitro migration and invasion assay, in vivo metastasis experiments, luciferase reporter assay and Chromatin immunoprecipitation. Results Transcriptome sequencing analysis revealed that epithelial cell adhesion molecule (EpCAM) was significantly decreased in Slug-overexpressing SiHa cells. Simultaneously, an absence of EpCAM expression was observed in Slug-overexpressing cells. Further studies revealed the trans-suppression effect of Slug on EpCAM through its binding to the E-boxes in the proximal promoter region of EpCAM in cervical cancer cells. Restoring EpCAM in Slug-overexpressing cells by transiently transfecting an EpCAM recombinant plasmid attenuated cell motility and promoted cell growth. Moreover, the negative correlation between Slug and EpCAM expression in human squamous cervical carcinoma (SCC) samples was verified by using Pearson correlation analysis. Conclusions These results demonstrated that the absence of EpCAM under Slug expression in cervical cancer cells probably participated in Slug-regulated EMT and further promoted tumor metastasis. Additionally, this study supports a potential way for Slug to initiate EMT progression in cervical cancer cells in addition to inhibiting E-cadherin.